Identity Meaning of a Gapura Wringinlawang at the Hinduism-Semeru Lumajang Temple - Rizal Ardy Firmansyah; Murni Rachmawati; Ima Defiana (Journal of Architecture & Environment, 2023)
Semiotics as a science that studies signs have a wide range of knowledge and one of them is in the field of Architecture which is a result of the cultural process of society because architectural works are the embodiment of the life of that society. Semiotics as the science of signs is capable of being a tool in tracing cultural relations in architectural objects or works. Pura Mandharagiri Semeru Agung as an architectural work that carries Balinese Hindu culture is an architectural work located at the foot of Mount Semeru, to be precise in an area called Senduro in Lumajang district. An architectural object in the form of a gate with the name Wringinlawang stands proudly at the entrance to the area. Wringinlawang in shape and color has a style that is different from the style in the temple area. Therefore, there is a need for a study related to the existence of the wringinlawang object in the middle of the temple area which carries Balinese Hindu culture. To trace the process of wringinlawang's existence and its meaning to the surrounding community, semiotics will be the main tool in tracing the sign, which in this case is the Gapura Wringinlawang. The purpose of this research is to explore the factors influencing the meaning of the Gapura Wringinlawang and to explore the relationship between the signs that are formed. The method used in this research is qualitative research using interview data alongside a literature review. The results of Charles S. Pierce's semiotic study show that the Gapura Wringinlawang contains a symbol of cultural identity for the Senduro community around the temple building. The culture in question is Javanese culture which is manifested through the building style used in the Gapura Wringinlawang building because of the context of the location.